Strategi Penerapan Prinsip Maqashid Syariah Dalam Pengelolaan Badan Usaha Milik Desa (Studi kasus di Badan Usaha Milik Desa Amanah Desa Bukit Gajah Kabupaten Pelalawan) - Syahrizul, Syahrizul; Pakkanna, Mukhaer (Jurnal Ilmiah Ekonomi Islam, 2024)
Abstract Badan Usaha Milik Desa Amanah is a business entity owned by the village and has 5 different business units. Although it has implemented sharia principles in the Financing Unit, there are still challenges in the overall implementation as it still partners with conventional banks. Therefore, research was conducted to develop a strategy for implementing Maqashid Syariah in the management of the Amanah Village-Owned Enterprise, using SWOT analysis. The research used a qualitative approach by analysing the application of Maqashid Syariah principles and in-depth interviews with various relevant parties. The research concluded that the Amanah Village-Owned Enterprise can implement Maqashid Sharia principles into its management by internalising indicators such as religious compliance, improving the quality of human resources, sharia management, business orientation seeking blessings and profits, and sharia financial management. The best strategy for the implementation of Maqashid Syariah principles is to revise the Articles of Association/Bylaws to become a Sharia-based Amanah Village-Owned Enterprise and increase partnerships with Bank Rakyat Indonesia and other partners.